2003
DOI: 10.4315/0362-028x-66.11.2076
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Bifidobacteria Encapsulated in Polysaccharide-Protein Gel Beads against Gastric Juice and Bile

Abstract: Bifidobacterium cells were encapsulated in a mixed gel composed of alginate, pectin, and whey proteins. Two kinds of capsules were obtained: gel beads without membranes and gel beads with two membranes formed by the transacylation reaction. In vitro studies were carried out to determine the effects of simulated gastric pH and bile salts on the survival of free and encapsulated Bifidobacterium bifidum. The protective effects of gel beads without membranes and gel beads coated with two membranes formed by the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(89 citation statements)
references
References 32 publications
6
80
0
3
Order By: Relevance
“…Researchers used high concentrations of gelatine (24 % w/v) to encapsulate L. lactis by crosslinking with toluene−2, 4-diisocyanate for biomass production (Hyndman et al, 1993). Moreover, encapsulation of Bifidobacterium cells in a mixed gel composed of alginate, pectin and whey proteins has been investigated (Guerin et al, 2003). As a result, the encapsulated cells survived better that free cells in simulated gastric pH and bile solutions.…”
Section: Gelatinementioning
confidence: 99%
“…Researchers used high concentrations of gelatine (24 % w/v) to encapsulate L. lactis by crosslinking with toluene−2, 4-diisocyanate for biomass production (Hyndman et al, 1993). Moreover, encapsulation of Bifidobacterium cells in a mixed gel composed of alginate, pectin and whey proteins has been investigated (Guerin et al, 2003). As a result, the encapsulated cells survived better that free cells in simulated gastric pH and bile solutions.…”
Section: Gelatinementioning
confidence: 99%
“…[164,165]. It has been shown that the optimum temperature for the development of probiotic strains is 35-40ºC and pH varies between 4,0 and 3,6 [6].…”
Section: Probiotic Bacteria In the Fermentation Of Fruit Vegetablesmentioning
confidence: 99%
“…It has been shown that the optimum temperature for the development of probiotic strains is 35-40ºC and pH varies between 4,0 and 3,6 [6]. To protect the cells from the effects of the environmental factors agar, alginate, chitosan are used [165,166,167]. A probiotic banana product fermented with Lactobacillus acidophilus, included in alginate gel structures, is obtained.…”
Section: Probiotic Bacteria In the Fermentation Of Fruit Vegetablesmentioning
confidence: 99%
“…It has been reported that the optimum probiotic growth temperature is between 35 and 40 °C, and the best pH is between 6.4 and 4.5, ceasing when a pH of 4.0-3.6 is reached [123]. This situation could be solved by using some supports, such as agar, polyacrylamide, calcium pectate gel, chemically-modified chitosan beads and alginates, to provide a physical barrier against unfavorable conditions [124][125][126].…”
Section: Biopreservation and The Use Of Probiotic Coatingsmentioning
confidence: 99%